THE INFLUENCE OF TEACHING MODELS AND REASONING ABILITY TOWARD WRITING SKILL - Effendi, M. Syahrun; Rafli, Zainal; Rahmat, Aceng (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The purposeof this experimental research is to figure out the influence of teaching model and reasoning ability toward students’ writing skill. The research was conducted at state elementary School 9 of Tanjung Batu - Ogan Ilir South Sumatra. The results show that: (1) students’ writing skill using Discovery Learning model is higher than the ones use Guided Learning model; (2) There is an interaction effect between the teaching model and reasoning ability toward writing skill, and (3) students’ writing skill with high reasoning ability and using Discovery Learning model is higher than the students using Guided Learning model, and (4) the level of students’ writing skill with low reasoning ability and using Discovery Learning model is less than the ones use Guided Learning.